Prevalencia de tabaquismo, alcoholismo y sedentarismo en estudiantes de medicina de una universidad privada de Medellín, 2014 (2015)
Introduction: Medical students are a group at high risk for sedentary, smoking and consumption of alcohol, these are health problems with high prevalence and multiple risk factors. Objective: To estimate the prevalence of smoking, consumption of alcohol and sedentary in medical students from a private university in Medellín-Colombia and their associated factors, 2014. Methods: Cross-sectional study on 224 individuals. The prevalence of smoking and alcoholism was based on Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) and sedentary with International Physical Activity Questionnaire (IPAQ). The analysis performed in SPSS 21.0® with frequencies, summary measures, nonparametric tests and binary logistic regression. Results: The prevalence of smoking in life was 47.8% and in the last three months of 20.1%; for alcohol use were 90.6% and 73.7%, respectively; the prevalence of sedentary was 62.9%. Correlation between sedentary and consumption of alcohol and smoking was found. The consumption of alcohol and smoking presented association with socioeconomic status, family functioning and consumption of a family member; alcohol consumption also presented association with the formation cycle. Factors associated with sedentary were gender and formation cycle. Conclusion: Is evident the simultaneity in the presentation of the three health problems, its high magnitude and diversity of associated factors; this may guide actions of prevention of disease, health promotion and subsequent analytical studies. © 2015 iMedPub.